If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 53 = 0.4(272) + 0.18(t + -272) Multiply 0.4 * 272 53 = 108.8 + 0.18(t + -272) Reorder the terms: 53 = 108.8 + 0.18(-272 + t) 53 = 108.8 + (-272 * 0.18 + t * 0.18) 53 = 108.8 + (-48.96 + 0.18t) Combine like terms: 108.8 + -48.96 = 59.84 53 = 59.84 + 0.18t Solving 53 = 59.84 + 0.18t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-0.18t' to each side of the equation. 53 + -0.18t = 59.84 + 0.18t + -0.18t Combine like terms: 0.18t + -0.18t = 0.00 53 + -0.18t = 59.84 + 0.00 53 + -0.18t = 59.84 Add '-53' to each side of the equation. 53 + -53 + -0.18t = 59.84 + -53 Combine like terms: 53 + -53 = 0 0 + -0.18t = 59.84 + -53 -0.18t = 59.84 + -53 Combine like terms: 59.84 + -53 = 6.84 -0.18t = 6.84 Divide each side by '-0.18'. t = -38 Simplifying t = -38
| 6.7x+5-9.7x=2 | | 5v/4=35 | | .75(x+6)=-2 | | Y=Hz+m | | 7x-56.4=x | | -2.3f=2.9 | | -4(5y-7)+2(4y+8)= | | C=.04(272)+.18(t-272) | | 8y-2x=20 | | 17+6k= | | 10/13n=30-/39 | | C=.04(272)+.18(627-272) | | 47-9(5xa)= | | 6y-17y=-29-37 | | -2/-6 | | 0.38=log(x/10) | | X+2(-2)=9 | | 12=10/x^2 | | -2(-3m+3)=6 | | 8/9o=12/18 | | 3x^(1/2)-4x^(1/4)=-1 | | 3/7h=12/35 | | 154*22= | | 4y+6x=-48 | | 14*11= | | -16.25=-5.6+m | | 0.25=0.5f | | 4x-3(-2x+13)=-19 | | 6(2x+3)=-3(x-2) | | 8(7a-7)=112 | | 6m^2=13n+28 | | 10+(w+7)=-12 |